(untitled) (Nexus International Journal of Science and Education, 2024)
Culturally responsive teaching is an educational approach that recognizes and values the diverse cultural backgrounds of learners. This qualitative study aims to investigate junior high school teachers' perceptions of the effects of culturally responsive teaching on the academic achievement of learners The results disclosed the abstract to explores the concept of culturally responsive teachers through various lenses, highlighting their content findings, implications, and future directions. The findings reveal that culturally responsive teachers acknowledge learners' cultural identities, employ inclusive curriculum, build meaningful connections, utilize instructional strategies that embrace diversity, and address social justice issues. The implications suggested that culturally responsive teaching promotes inclusive and equitable education, enhances learner engagement and academic achievement, develops cultural competence, and fosters positive social-emotional development. Future directions emphasize continuous professional development, integration of technology, collaboration and cultural exchange, intersectionality and multiple identities, incorporation of student voice, research and evaluation, policy and systemic changes, family and community engagement, and global perspectives. The results highlight the transformative potential of culturally responsive teachers in creating inclusive and empowering educational experiences for all learners, identifying areas for further exploration and growth in the field, also provides insights into the potential impact of culturally responsive teaching practices on teacher attitudes and practices in the Philippines.